Innovations In Perinatal Healthcare Delivery And Their Impact On Maternal And Neonatal Outcomes - Geetharani, Dr. Ramisetty; M, Kavitha; Narasimhan, Balamurugan; Branson, Bennett Benjamin (Adolescência e Saúde, 2026)
Background: The perinatal field is experiencing innovations in perinatal healthcare delivery, such as telemedicine, artificial intelligence, and mobile health interventions, which are changing the nature of maternal and neonatal care, especially in resource-constrained systems, where access to quality care is still low. Objective: The proposed study will help assess how innovative healthcare delivery methods will affect maternal and neonatal outcomes with the identified outcomes being the measures of accessibility, early diagnosis, and mortality reduction. Methodology: A systematic review method was used to search the peer-reviewed literature published during the period (2015-2025) and the global health reports were analyzed. They included studies that evaluated interventions on technology and system level in perinatal care with quantifiable outcome. Findings: The review reveals that telemedicine interventions helped to boost attendance rates at antenatal care by around 25-40 percent, and AI-assisted diagnostic tools helped to boost the levels of early detection of the high-risk pregnancy by 30 percent. Mobile health (mHealth) interventions led to improved intervention engagement and compliance and were associated with a 15-25 percent decrease in maternal complications. The neonatal mortality rates at some locations decreased by almost 20% because of integrated care models. Conclusion: Perinatal healthcare delivery innovations are highly beneficial in improving maternal outcomes and neonatal outcomes in terms of access, early diagnosis, and follow-up. The differences in infrastructure and access to digital facilities have to be, however, addressed to see an equal application.